An Algorithm for the Retrieval of Aerosol Optical Depth from Geostationary Satellite Data in Thailand - Masiri, Itsara; Janjai, Serm; Jantarach, Treenuch (Journal of the Institute of Engineering, 2012)
An algorithm was developed to estimate aerosol optical depth (AOD) from geostationary satellite data. The 6S radiative transfer computer code was employed to generate a look-up table (LUT) which incorporates several combinations of satellite-derived variables including earthatmospheric reflectivity, atmospheric reflectivity and surface albedo. The parameterization of the satellite-derived atmospheric reflectivity accounted for the scattering of solar radiation by clouds, absorption of solar radiation by water vapour, ozone and gases and solar radiation depletion by aerosols. The digital data of the MTSAT-1R satellite were used as the main input of the algorithm. For the validation, the values of AOD derived from this algorithm were compared with those obtained from four sites of Aerosol Robotic Network (AERONET) in Thailand, and a reasonable agreement was found. DOI: http://dx.doi.org/10.3126/jie.v8i3.5929 JIE 2011; 8(3): 32-41